Pengaruh E-recruitment, Reputasi Perusahaan, dan Kompensasi terhadap Intensi Melamar Kerja Generasi Z di Kota Magelang - Nadia Ismi Chanifah; Hanung Eka Atmaja; Dian Marlina Verawati (J-MIND (Jurnal Manajemen Indonesia), 2025)
This study aims to examine the relationship between e-recruitment, company reputation, and compensation and the job application intention of Generation Z in Magelang City. The research employs a quantitative approach with a population consisting of individuals born between 1997 and 2012, representing Generation Z, aged 12 to 27 years. A total of 160 respondents were selected using purposive sampling. Data were collected through an online questionnaire and analyzed using multiple regression with SPSS version 26. The results indicate that e-recruitment, company reputation, and compensation jointly influence job application intention. However, when tested individually, e-recruitment and company reputation have a significant positive effect on job application intention, whereas compensation shows no significant effect.